Compression test of multi-scale modified concrete and application of novel damage variable in concrete performance analysis. (December 2022) - Cheng, Shitao; He, Haoxiang; Tian, Shuyu; Cheng, Yang
Abstract: To change the characteristics of brittle failure and easy cracking of the concrete, a novel method of mixing materials with different scales into concrete to inhibit the generation and development of cracks is proposed. Taking carbon nanotubes (CNTs), calcium carbonate whisker (CCW), polyvinyl alcohol (PVA) fiber, steel fiber and rubber particles as the experimental materials, the multi-scale modified concrete compression test was carried out. According to the test results, the effects of different materials on the mechanical properties of concrete are analyzed, and the optimal content scheme of materials is determined. In view of the damage constitutive and damage variables based on the Weibull distribution cannot comprehensively reveal the mechanical properties and damage state of concrete, the combined damage variable, the damage variable based on energy method and the corresponding damage constitutive model are presented. To synthetically evaluate the mechanical properties of concrete from the perspective of damage, the modified damage variable is proposed considering the influence of concrete compressive strength. The analysis results show that the optimal content of CNTs, CCW, PVA fiber, steel fiber and rubber particles are 0.6%, 6%, 0.075%, 1% and 0%, respectively. The damage variable based on the energy method has a clear damage mechanism and can accurately represent the performance state of concrete. The modified damage variable can significantly distinguish the comprehensive performance of different concretes. In addition, the scanning electron microscope results verified that CNTs, CCW, PVA fiber and steel fiber can inhibit the development of cracks through the bridging effect to change the failure pattern of concrete.